2003
DOI: 10.1002/lsm.10179
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of an Er:YAG laser, a GaAlAs diode laser, and scaling and root planing on periodontally diseased root surfaces: A comparative histologic study

Abstract: The present in vivo results showed that (i) ERL, combined with a fluorescent calculus detection system, provided a selective subgingival calculus removal on a level equivalent to that provided by SRP, and (ii) DL, using this power output, was unsuitable for calculus removal and altered the root surface in an undesirable manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(120 citation statements)
references
References 39 publications
2
103
1
13
Order By: Relevance
“…A.Actinomycesmcomitans has alsobeen found in atherosclerotic plaques, and there has been evidence to suggest that sub gingival A. Actinomycesmcomitans may be related to coronary heart disease.This makes it even more compelling to seek methods to control this aggressive pathogen [24].Laser soft tissue treatment for pericoronal infections has the effect on CFU which is clear in reducing bacterial loads. Due to its characteristics, as well as to other known advantages such as low cost and practicality, the diode laser has been compared to the other conventional methods [25].It has been subject of a diversity of studies intended to evaluate its potential in relation to its biocompatibility [26].…”
Section: Imentioning
confidence: 99%
“…A.Actinomycesmcomitans has alsobeen found in atherosclerotic plaques, and there has been evidence to suggest that sub gingival A. Actinomycesmcomitans may be related to coronary heart disease.This makes it even more compelling to seek methods to control this aggressive pathogen [24].Laser soft tissue treatment for pericoronal infections has the effect on CFU which is clear in reducing bacterial loads. Due to its characteristics, as well as to other known advantages such as low cost and practicality, the diode laser has been compared to the other conventional methods [25].It has been subject of a diversity of studies intended to evaluate its potential in relation to its biocompatibility [26].…”
Section: Imentioning
confidence: 99%
“…31 In addition to chemical conditioning, the applicability of different laser systems such as CO 2 , Nd:YAG, diode and Er:YAG laser in the removal of the smear layer have been demonstrated. [32][33][34][35][36][37][38][39][40][41][42][43] However, until now, no published data have been available concerning the clinical outcomes following root surface biomodification with Nd:YAG laser for the treatment of gingival recession. Therefore, the aim of the present study was to evaluate and compare the outcome of gingival recession therapy using the SCTG with or without Nd:YAG laser application for root surface biomodification.…”
mentioning
confidence: 99%
“…22 Schwartz et al showed that the efficacy of calculus removal by Er:YAG laser irradiation in the clinical setting was similar to that of hand instruments; but, diode laser irradiation was not suitable for calculus removal due to significant surface distortion caused. 23 Frentzen et al reported increased loss of cementum and dentin and high surface roughness due to Er:YAG laser irradiation and questioned its clinical application. 24 On the other hand, de Mendonca et al in 2008 reported that SRP with manual curettes caused rougher surfaces than Er:YAG laser irradiation and ultrasonic scaler, and added that all methods increased root surface roughness after treatment.…”
Section: Discussionmentioning
confidence: 99%